Research on nutrient flows and balances in East and Southern Africa: state-of-the-art - Nandwa, S.M; Bekunda, M.A (Agriculture, ecosystems & environment, 1998)
East and Southern Africa have soils that are still relatively fertile, notably those in the Highlands, associated with the Rift valley area. The lower areas are less well-endowed when it comes to soil fertility. At low agricultural intensity, this does not matter as nutrients cycle through the soil and the natural vegetation and losses are few. However, the past decades have shown high population increases, the adoption of continuous cultivation in areas that used to be under traditional shifting cultivation, and a decline of land productivity. The present review paper shows how much we know about the severity of this process and the technologies at hand that can stop it. The information provided shows that on the technical side much is known now, but research output is still poorly integrated into development. Although integrated nutrient management has been shown to be a panacea to combat nutrient depletion, there is a serious crisis of primary data on this subject.